Protective effect of syringic acid on kidney ischemia-reperfusion injury. (20th April 2016) - Sancak, Eyup Burak; Akbas, Alpaslan; Silan, Coskun; Cakir, Dilek Ulker; Turkon, Hakan; Ozkanli, Sidika Seyma
Abstract: The objective of the present study was to determine whether preischemic administration of syringic acid (SA) would attenuate renal ischemia-reperfusion injury (IRI). Rats were divided into three groups: Sham group; IR group; and IR + SA group. The effects of SA were examined using biochemical parameters including serum ischemia-modified albumin (IMA), total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), tissue superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT) and malondialdehyde (MDA). The apoptosis status and histopathological changes were evaluated. After calculating the score for each histopathological change, the total score was obtained by summing all the scores. In the SA group, MDA, IMA, TOS, and OSI decreased significantly compared to the IR group. After SA administration, the increase in GPx activity was found to be significant. Apoptosis decreased significantly in the SA group compared with the IR group. The total score significantly decreased after administration of SA. Taken together, our findings suggest that SA preconditioning is effective in reducing tissue damage induced in kidney IRI. Renal histology also showed convincing evidence regarding the protective nature of SA.